The asymmetric implementation of the European Banking Union (EBU): Consequences for financial stability - Uwe Vollmer (International Journal of Management and Economics, 2016)
EU Member States outside the Eurozone are hesitating to enter the European Banking Union (EBU) and to establish "close cooperation" in bank supervision with the ECB. This paper analyzes the consequences of such asymmetric integration for financial stability in Europe. It argues that the main obstacles against establishing close cooperation are a lack of voting rights and insufficient access to the fiscal backstop provided by the European Stability Mechanism (ESM). The paper presents arguments as to why international cooperation in bank supervision could be welfare improving, if multinational banks are dominant. It also discusses suitable reform options for making it more attractive for EU Member States to begin a close cooperation with the ECB.
Keywords: G38; G21; F36; 650; multinational banking; capital requirements; bank resolution; regulatory arbitrage